The personal diaries and the notes of the pedagogical travels of Rosa Sensat Vilà during the period 1908-1913: critical and conceptual analysis, contributions and debates - Soler Mata, Joan (Historia y Memoria de la Educación, 2019)
The article is focused on the critical and conceptual analysis of the personal diaries and the travel notes, with pedagogical character, that the teacher Rosa Sensat Vila (1873-1961) made during the period 1908-1913 in different European countries. We ask ourselves about the people and the places, about the personal and relevant experiences and the opinions and the critical reviews in personal diaries in order to rebuild a part of the process of elaboration of the conceptual universe of Rosa Sensat. The documentary sources are a primary and written nature. They are located in the Fons Històric of the Rosa Sensat Library in Barcelona and in the Archivo Edad de Plata (Fondo JAE). The qualitative methodology is a hermeneutic and conceptual nature, taking into account some contributions of biographical-narrative research. From Reading of personal diaries and travel notes, we locate and systematize the data and available information with the aim of establishing a catalogue of the institutions and the relationships with European teachers; and also to interpret the texts and the descriptions to analyze the ideas and, above all, the concepts that it incorporates to its own pedagogical ideology.